A cross-sectional survey of general practice health workers' perceptions of their provision of culturally competent services to ethnic minority people with diabetes. Issue 6 (December 2018) - Zeh, Peter; Cannaby, Ann-Marie; Sandhu, Harbinder K.; Warwick, Jane; Sturt, Jackie A.
Highlights: 56% GP practices provided highly culturally-competent diabetes services. 32% City GP staff spoke a second language relevant to the practice's minority population. GP staff from minority groups were 1:5 compared to 1:10 in the city's population. 100% GP practice staff received regular formal training on diabetes care. No GP practice staff received formal/structured cultural competence training. Abstract: Aims: To explore General Practice teams cultural-competence, in particular, ethnicity, linguistic skillset and cultural awareness. The practice teams' access to diabetes-training, and overall perception of cultural-competence were also assessed. Methods: A cross-sectional single-city-survey with one in three people with diabetes from an ethnic minority group, using 35 semi-structured questions was completed. Self-reported data analysed using descriptive statistics, interpreted with reference to the Culturally-Competent-Assessment-Tool. Results: Thirty-four (52%) of all 66 practices in Coventry responded between November 2011 and January 2012. Key findings: (1) One in five practice staff was from a minority group in contrast with one in ten of Coventry's population, (2) 164 practice staff (32%) spoke a second language relevant to the practice's minority population, (3) 56% of practices were highly culturally-competent at providing diabetes services for minority populations, (4) 94% of practices reported the ethnicity of their populations, and (5) the most frequently stated barriers to culturally-competent service delivery were language and knowledge of nutritional habits. Conclusions: Culturally-competent diabetes care is widespread across the city. Language barriers are being addressed, cultural knowledge of diabetes-related-nutrition requires further improvement. Further studies should investigate if structured cultural-competence training for diabetes service providers produces positive effects in diabetes-related outcome-measures in minority populations.